2019
DOI: 10.1002/sctm.18-0284
|View full text |Cite
|
Sign up to set email alerts
|

EP4 Antagonist-Elicited Extracellular Vesicles from Mesenchymal Stem Cells Rescue Cognition/Learning Deficiencies by Restoring Brain Cellular Functions

Abstract: Adult brains have limited regenerative capacity. Consequently, both brain damage and neurodegenerative diseases often cause functional impairment for patients. Mesenchymal stem cells (MSCs), one type of adult stem cells, can be isolated from various adult tissues. MSCs have been used in clinical trials to treat human diseases and the therapeutic potentials of the MSC‐derived secretome and extracellular vesicles (EVs) have been under investigation. We found that blocking the prostaglandin E 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 115 publications
(154 reference statements)
0
42
0
Order By: Relevance
“…Here we further investigate whether the effects of EP 4 antagonist‐induced MSC EVs/exosomes on damaged brains also act on neuronal precursors and neurons. As described previously, bone marrow MSCs were characterized by their surface marker profiles and their abilities to differentiate into adipocytes and osteocytes before being subjected to EV and GW EP 4 antagonist‐induced MSC EVs/exosome (GWEV) collection . Four‐day pretreatment with GWEVs significantly increased the neurosphere‐forming ability of mouse NE‐4C NSCs, whereas pretreatment with basal MSC EVs did not increase neurosphere formation (Figure A; Figure S1A).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Here we further investigate whether the effects of EP 4 antagonist‐induced MSC EVs/exosomes on damaged brains also act on neuronal precursors and neurons. As described previously, bone marrow MSCs were characterized by their surface marker profiles and their abilities to differentiate into adipocytes and osteocytes before being subjected to EV and GW EP 4 antagonist‐induced MSC EVs/exosome (GWEV) collection . Four‐day pretreatment with GWEVs significantly increased the neurosphere‐forming ability of mouse NE‐4C NSCs, whereas pretreatment with basal MSC EVs did not increase neurosphere formation (Figure A; Figure S1A).…”
Section: Resultsmentioning
confidence: 80%
“…We previously showed that EP 4 antagonist‐induced MSC EVs/exosomes (GW MSC EVs/exosomes) have suppressive effects on both reactive astrocytes and active microglia; these suppressive activities contribute to the regenerative effects of the GW MSC EVs/exosomes on damaged brains . Here we further investigate whether the effects of EP 4 antagonist‐induced MSC EVs/exosomes on damaged brains also act on neuronal precursors and neurons.…”
Section: Resultsmentioning
confidence: 87%
“…Previous research from the laboratory of Hua‐Jung Li (National Health Research Institutes, Zhunan, Taiwan) demonstrated that EP4 antagonist‐induced MSC exosomes possessed a greater ability to rescue cognition and learning deficiencies caused by hippocampal damage . In their new Stem Cells Translational Medicine article, the team now report on the MSC exosome‐derived components that prompt these improved regenerative effects.…”
Section: Featured Articlesmentioning
confidence: 99%
“…Previous studies from the laboratory of Hua‐Jung Li (National Health Research Institutes, Miaoli, Taiwan, China) discovered that blocking prostaglandin E2/prostaglandin E2 receptor 4 signaling in mammary epithelial stem cells prompted the secretion of extracellular vesicles with the ability to induce mouse mammary gland formation . In their new study in Stem Cells Translational Medicine , the team sought to discover if blocking this pathway in MSCs could also promote the release of proregenerative extracellular vesicles for the treatment of the impairments in cognition, learning, and memory observed following the hippocampal damage associated with central nervous system diseases and traumatic brain injury. Chen et al revealed that treating MSCs with a prostaglandin E2 receptor 4 antagonist prompted the secretion of extracellular vesicles carrying a cargo of anti‐inflammatory cytokines and factors with the potential to modulate astrocyte function, blood–brain barrier integrity, and microglial migration into the damaged hippocampus.…”
Section: Featured Articlesmentioning
confidence: 99%
“…Said strategies currently include mesenchymal stem cell (MSC)‐based treatments; however, studies have suggested that implanted MSCs do not differentiate into replacement tissues, thereby proposing paracrine signaling and the enhanced activity of endogenous repair mechanisms as the primary therapeutic mechanisms of MSCs post‐transplantation . In our first Featured Article in Stem Cells Translational Medicine this month, Chen et al discovered that blocking a specific signaling pathway in MSCs promoted the release of extracellular vesicles with the ability to significantly reduce the damaging consequences of hippocampal damage in mice . In a Related Article from Stem Cells , Leeson et al report on how the P2X7 receptors expressed by adult murine hippocampal NPCs control cell death, niche formation, and cell proliferation and thereby influence adult neurogenesis .…”
mentioning
confidence: 99%